Study in the Quality of Clinical Documentation Practice in Chitwan Medical College Teaching Hospital, Nepal - Pandit, Upendra (Journal of Nepalgunj Medical College, 2016)
Background: Primary documentation of a patient is crucial for making effective healthcare decision and improvements in the quality of care. The objective of this study was to assess the quality of current documentation practice in tertiary care hospitals. Materials and methods: This was an assessment of medical documentation practice of one year from the period of January 2010 to December 2010 in Chitwan Medical College, Teaching Hospital. Total 184 patients' discharge files were enrolled and reviewed. Documentation was reviewed in its quality such as completeness, Coherent, consistency and Legibility.Results: In overall pooled analysis, High omission rate was observed in final diagnosis, results (cure, improved, referral and death), hospital stay, and final case summary. Although, satisfactory performance was observed in complete set of forms (72.2%); Patient consent for treatment &release authorization forms (78.2%) and treatment chart (60.8%), the overall pooled performance in ten components showed50% performance gap. Study demonstrated that documentation and its legibility, coherent and consistency in all departments needs substantial improvements in the institution.JNGMC Vol. 12 No. 2 December 2014, Page: 11-16